2011
DOI: 10.1542/peds.2010-2590
|View full text |Cite
|
Sign up to set email alerts
|

Fermented Milk Containing Bifidobacterium lactis DN-173 010 in Childhood Constipation: A Randomized, Double-Blind, Controlled Trial

Abstract: WHAT'S KNOWN ON THIS SUBJECT:Chronic constipation is a common problem in childhood. In two randomized trials in adults with irritable bowel syndrome and constipation, and 1 in constipated women with a defecation frequency Ͻ3 times per week, a significant increase was shown in stool frequency in the probiotic group who used Bifidobacterium lactis DN-173 010 compared with the control group in subjects who had Ͻ3 stools per week. WHAT THIS STUDY ADDS:In constipated children, the fermented dairy product that conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
71
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 22 publications
0
71
0
6
Order By: Relevance
“…However, most of the traditional fermented to help alleviate constipation (Tabbers et al, 2011). Additionally, they have been shown to have 268 modulatory effects on the brain, and demonstrate anti-cancer potential (Kumar et al, 2012; 269 Tillisch et al, 2013 (Hugenholtz, 2013).…”
mentioning
confidence: 99%
“…However, most of the traditional fermented to help alleviate constipation (Tabbers et al, 2011). Additionally, they have been shown to have 268 modulatory effects on the brain, and demonstrate anti-cancer potential (Kumar et al, 2012; 269 Tillisch et al, 2013 (Hugenholtz, 2013).…”
mentioning
confidence: 99%
“…The proteolysis that occurs in fermenting milk results in a higher content of peptides and free amino acids, especially cystine, histidine, and asparagine, which play various roles in health, and produce a more digestible food than milk per se [22]. The breakdown of lactose by the bacteria containing β-galactosidase in the fermentation process allows many lactoseintolerant individuals to consume the milk product [23]. Lactic acid bacteria have the ability to re-synthesize vitamins such as folate that were destroyed by milk pasteurization that occurs prior to fermentation [24].…”
Section: Benefits Of Fermented Milksmentioning
confidence: 99%
“…Subjects were divided into two groups, 20 subjects (50%) were given placebo and 20 subjects (50%) were given L. reuteri, and there was no drop out subject. Ranges of Agachan scores before treatment in placebo and L. reuteri group are 16.00 (15-19), dan 17.00 (16)(17)(18)(19)(20) Table 1.…”
mentioning
confidence: 99%
“…Coccurullo et al, Tabbers et al, and An et al reported and consistency of defecation in patients taking probiotics. 16,18,19 This research was conducted because of the differences in the reported results of various studies on the use of L. reuteri in chronic constipation patients, and the lack of research on chronic constipation in adult patients which were assessed based on various aspects of constipation.…”
mentioning
confidence: 99%